2011
DOI: 10.1039/c0an00931h
|View full text |Cite
|
Sign up to set email alerts
|

Optical imaging in tissue with X-ray excited luminescent sensors

Abstract: We report a high-spatial resolution imaging technique to measure optical absorption and detect chemical and physical changes on surfaces embedded in thick tissue. Developing sensors to measure chemical concentrations on implanted surfaces through tissue is an important challenge for analytical chemistry and biomedical imaging. Tissue scattering dramatically reduces the resolution of optical imaging. In contrast, X-rays provide high spatial resolution imaging through tissue but do not measure chemical concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…[15] The ability of X-ray excited optical luminescence to study silver dissolution through tissue in one dimension was also demonstrated. [16] We also showed that hollow X-ray scintillators could be used to monitor drug release in vitro and the luminescent signal could be detected at one wavelength in living mice, however, luminescent signal was detected by only irradiating a single location in living mice (not a scanned or two dimensional image) and no in vivo drug release monitoring was achieved. [17] Herein, we extended our previous work and developed an XELCI technique to non-invasively map local pH variation due to bacterial metabolic activity in two dimensions through thick tissue with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…[15] The ability of X-ray excited optical luminescence to study silver dissolution through tissue in one dimension was also demonstrated. [16] We also showed that hollow X-ray scintillators could be used to monitor drug release in vitro and the luminescent signal could be detected at one wavelength in living mice, however, luminescent signal was detected by only irradiating a single location in living mice (not a scanned or two dimensional image) and no in vivo drug release monitoring was achieved. [17] Herein, we extended our previous work and developed an XELCI technique to non-invasively map local pH variation due to bacterial metabolic activity in two dimensions through thick tissue with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%
“…This term captures sensing methods of physical and chemical changes of functionalized surfaces within tissue. An example is described by Chen et al [22] where a phosphor layer was sandwiched in between a thin silver deposit and structural substrate and inserted into pig tissue. X-Ray excited visible phosphor luminescence was adequately transmitted so as to be detected outside the tissue.…”
Section: Introductionmentioning
confidence: 98%
“…Typical x-ray contrast agents are highly concentrated aqueous solutions (typically iodine-based), and thus cannot be employed for molecular imaging due to their high viscosity and limits on osmolality [5]. To further investigate the molecular imaging potentials for x-ray imaging, x-ray luminescence computed tomography (XLCT) has recently been studied and developed by several groups, including ours [24, 617]. …”
Section: Introductionmentioning
confidence: 99%